Chemical Diversity as a Function of Temperature in Six Northern Diatom Species - Siv Huseby; Maria Degerlund; Gunilla K. Eriksen; Richard A. Ingebrigtsen; Hans Chr. Eilertsen; Espen Hansen (Marine Drugs, 2013)
In this study, we investigate how metabolic fingerprints are related to temperature. Six common northern temperate diatoms (Attheya longicornis, Chaetoceros socialis, Chaetoceros furcellatus, Porosira glacialis, Skeletonema marinoi, and Thalassiosira gravida) were cultivated at two different temperatures, 0.5 and 8.5 °C. To exclude metabolic variations due to differences in growth rates, the growth rates were kept similar by performing the experiments under light limited conditions but in exponential growth phase. Growth rates and maximum quantum yield of photosynthesis were measured and interpreted as physiological variables, and metabolic fingerprints were acquired by high-resolution mass spectrometry. The chemical diversity varied substantially between the two temperatures for the tested species, ranging from 31% similarity for C. furcellatus and P. glacialis to 81% similarity for A. longicornis. The chemical diversity was generally highest at the lowest temperature.